2016
DOI: 10.1007/s10753-016-0329-z
|View full text |Cite
|
Sign up to set email alerts
|

Does Inflammation Mediate the Association Between Obesity and Insulin Resistance?

Abstract: In adult obesity low-grade systemic inflammation is considered an important step in the pathogenesis of insulin resistance (IR). The association between obesity and inflammation is less well established in adolescents. Here, we ascertain the importance of inflammation in IR among obese adolescents by utilizing either Random Forest (RF) classification or mediation analysis approaches. The inflammation balance score, composed of 8 pro- and anti-inflammatory makers, as well as most of the individual inflammatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 29 publications
1
30
0
Order By: Relevance
“…Our results increase the confidence that continued probing into this area will eventually unearth the specific biological mechanisms that underlie the associations between obesity and episodic memory as well as other aspects of executive function. One candidate mechanism of impaired cognitive function resulting from the accumulation of visceral fat is the secretion of pro-inflammatory cytokines which can result in insulin resistance and worsen cerebrovascular reactivity ( Adabimohazab et al, 2016 ; Lambert et al, 2015 ; Miller & Spencer, 2014 ). Another possible mechanism for the impairment of cognitive functioning is central and adipose inflammation which plays a significant role in reduced synaptic plasticity ( Erion et al, 2014 ; Willette & Kapogiannis, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our results increase the confidence that continued probing into this area will eventually unearth the specific biological mechanisms that underlie the associations between obesity and episodic memory as well as other aspects of executive function. One candidate mechanism of impaired cognitive function resulting from the accumulation of visceral fat is the secretion of pro-inflammatory cytokines which can result in insulin resistance and worsen cerebrovascular reactivity ( Adabimohazab et al, 2016 ; Lambert et al, 2015 ; Miller & Spencer, 2014 ). Another possible mechanism for the impairment of cognitive functioning is central and adipose inflammation which plays a significant role in reduced synaptic plasticity ( Erion et al, 2014 ; Willette & Kapogiannis, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies indicate that inammation occurs due to an imbalance between the pro-and anti-inammatory cytokines that play a vital role in etiopathogenesis in obesity. 93,94 Elevated oxidative stress and impaired blood lipids are responsible for the release of pro-inammatory cytokines (such as TNF-a and ILs) directly into primary adipocytes and macrophages. 95,96 It has been well reported that hypertrophy in adipocyte cells result in macrophage inltration and the increased production of ROS as well as proin-ammatory cytokines in obese conditions; 97,98 thus, several lines of evidence suggest the role of pro-inammatory cytokines in regulating obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin resistance (or reduced insulin sensitivity) is characterized by suboptimal biological responses of the liver, skeletal muscle and adipose tissue to normal amounts of insulin secreted [ 4 , 5 , 17 19 ]. Several biological processes such as glucose, lipid or protein metabolism as well as single hormonal effects such as glycogen synthesis or glucose oxidation may be affected in this condition [ 20 , 21 ]. Several factors may contribute to insulin resistance in CKD.…”
Section: Discussionmentioning
confidence: 99%